1992
DOI: 10.1111/j.1365-2249.1992.tb05872.x
|View full text |Cite
|
Sign up to set email alerts
|

An early defect in primary and secondary T cell responses in asymptomatic cats during acute feline immunodeficiency virus (FIV) infection

Abstract: SUMMARYAs in HIV infection of humans, cats infected with FIV are particularly susceptible to secondary infection by opportunistic pathogens, suggesting an impaired ability to elicit an effective immune response against foreign antigens. In order to investigate the development of immunity in FIVinfected cats, we have used an autologous culture system to directly measure priming of naive CD4+ T eells to soluble protein antigen, in vitro. Using this assay, we showed previously that cats infeeted with FIV for seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In addition, other immunologic abnormalities can be found. Lymphocytes may lose the ability to proliferate in response to stimulation with mitogens or antigens, and priming of lymphocytes by immunogens may be impaired [105,133,134,135,136,137,138,139]. Lymphocyte function may be reduced by altered expression of cell surface molecules, such as CD4, major histocompatibility complex II antigens, or cytokines and cytokine receptors [140,141,142,143,144], or through over-expression of abnormal molecules, such as receptors [145], leading to disrupted production of cytokines or receptor function.…”
Section: Clinical Signsmentioning
confidence: 99%
“…In addition, other immunologic abnormalities can be found. Lymphocytes may lose the ability to proliferate in response to stimulation with mitogens or antigens, and priming of lymphocytes by immunogens may be impaired [105,133,134,135,136,137,138,139]. Lymphocyte function may be reduced by altered expression of cell surface molecules, such as CD4, major histocompatibility complex II antigens, or cytokines and cytokine receptors [140,141,142,143,144], or through over-expression of abnormal molecules, such as receptors [145], leading to disrupted production of cytokines or receptor function.…”
Section: Clinical Signsmentioning
confidence: 99%
“…As well as a quantitative decline in CD4 ' T lymphocytes in FIV infection, we have also shown an early qualitative defect in CD4 ' T cell ("unction in asymptomatic cats which precedes the loss of CD4' cells [5]. Our previous studies have demonstrated ihat in addition to depressed proliferation of metnory T celts to secondary recall antigen [6], primary proliferation of naive CD4' T ceils to foreign protein antigen is significantly impaired in infected cats [5.6].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated ihat in addition to depressed proliferation of metnory T celts to secondary recall antigen [6], primary proliferation of naive CD4' T ceils to foreign protein antigen is significantly impaired in infected cats [5.6]. The defect in proliferation of the naive CD4' T cell subset precedes a ftinclioiial dclccl in memory CD4+ T cells [5]. Both the in vitro depletion and proliferative defects seen during FIV infection could be explained by the induction offCDinvilni.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In infections with other lentiviruses such as HIV and FIV, it is well established that host immune functions are often suppressed prior to more obvious alterations in circulating lymphocyte numbers or development of clinical disease , Miedema et al, 1988, Bishop et al, 1992. Despite ongoing conjecture about the potential of BIV to cause immunosuppression In cattle (Brownlie et al, 1994), as well as the potential value of BIV as a model for other lentiviruses such as HIV, there have been few controlled studies of the effects of BIV infection on acquired immune responses.…”
Section: Effects On Acquired Immunitymentioning
confidence: 99%